The past, present, and future evolution of Aurora Subglacial Basin’s subglacial drainage system - Anna-Mireilla Hayden; Tyler Pelle; Christine F. Dow (Nature Communications)
Abstract Aurora Subglacial Basin (ASB) in East Antarctica is among the most rapidly changing regions in Antarctica. Beneath the ASB, subglacial drainage networks allow for fast ice flow and facilitate mass losses by eroding the coastal ice shelves. The ASB underwent advance-retreat cycles since its inception 34 million years ago, and projections rely on these findings to predict future ice behaviour. Yet, these hindcasts and forecasts seldom consider the effects of subglacial drainage. Here, we model subglacial drainage networks and ice shelf basal melting of the ASB from 34 million years ago to 2100 CE. Our results indicate continual reorganisation of ASB drainage systems and ice shelf melt patterns, suggesting that the past does not fully serve as an analogue for the future. Since subglacial drainage accounts for up to 70% of ice shelf melt, our results imply that subglacial hydrology could trigger higher rates of mass loss than previously suggested.